2004
DOI: 10.1002/nur.20012
|View full text |Cite
|
Sign up to set email alerts
|

“I couldn't think that far”: Infertile women's decision making about multifetal reduction

Abstract: In this phenomenological study women's experiences regarding their decisions to undergo or forgo multifetal reduction of their higher-order multiple pregnancies were explored. Seven women who had conceived higher-order multiple pregnancies as the result of in vitro fertilization were interviewed. Four participants accepted reduction, whereas three participants declined. Three themes were discerned: (a) the presence of infertility as a barrier to contemplating hyperfertility; (b) multiple-birth pregnancy as yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The findings described above are the same as the current research. Their subjects showed psychological distress, and were exposed to moral and ethical dilemmas by fetal reduction (Collpy, 2004;Maifeld et al, 2003). This it becomes readily apparent that the situation of medical/surgical fertility procedures has triggered powerful psychological impacts side by side with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings described above are the same as the current research. Their subjects showed psychological distress, and were exposed to moral and ethical dilemmas by fetal reduction (Collpy, 2004;Maifeld et al, 2003). This it becomes readily apparent that the situation of medical/surgical fertility procedures has triggered powerful psychological impacts side by side with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Garel et al (1997) found in a study of 18 pregnant women deciding on fetal reduction that 12 felt extreme stress, suffered great pain and wanted to escape. After fetal reduction, women's persistent feelings of sadness and guilt may continue (Collpy, 2004). Studies such as McKinney, Downey and Timor-Tritsch (1995) found that after fetus reduction, 18% of women will miss the fetus, and 70% mourn killing it for up to three months.…”
Section: The Psychological Effects Of Fetal Reductionmentioning
confidence: 97%
“…Eventually, the frequency of fetal reductions stemming from assisted reproduction treatment allow clinicians to ensure that couples have a certain level of preparedness that is impossible in the context of selective termination ( Table 2). However, despite precautions taken by doctors in fertility clinics and by official authorities, several studies reveal that couples requesting assisted reproduction treatment assimilate the information on the risks of multiple pregnancy poorly and also hence the possibility of having recourse to fetal reduction (Collopy, 2004). It would seem that couples are too absorbed in their desire to have children and tend to consider the possibility of multiple pregnancy as unlikely (Collopy, 2004).…”
Section: Preparednessmentioning
confidence: 99%
“…However, despite precautions taken by doctors in fertility clinics and by official authorities, several studies reveal that couples requesting assisted reproduction treatment assimilate the information on the risks of multiple pregnancy poorly and also hence the possibility of having recourse to fetal reduction (Collopy, 2004). It would seem that couples are too absorbed in their desire to have children and tend to consider the possibility of multiple pregnancy as unlikely (Collopy, 2004). Moreover, some women consider themselves as 'too infertile' to develop such pregnancies (Collopy, 2004).…”
Section: Preparednessmentioning
confidence: 99%
“…(p. 128) Infertile women who become pregnant with the help of ART often have to make heartbreaking decisions about multifetal reduction (MFR). Collopy (2004) identified themes including the presence of infertility as a barrier to contemplating hyperfertility, multiple-birth pregnancy as another form of loss for infertile women, and the lasting effects for having made the decision. These women felt such a sense of irony because they had been desperate to conceive and now were making a decision about destroying a life.…”
Section: Coping With Infertilitymentioning
confidence: 99%